Revisiting a Remedy Against Chains of Unkindness - Wendelin Schnedler; Nina Stephan (ZBW – Leibniz Information Centre for Economics, 2020)
Previous experiments observe a chain of unkindness: unkindly treated people treat an innocent third party unkindly. As a remedy, it has been proposed that the unkindly treated person engages in emotional regulation by writing a letter to the unkind person. Indeed, subjects who received little money were willing to leave more to a third person when they were writing a letter rather than waiting. Here, we examine whether emotional regulation is indeed behind this observation. In line with emotional regulation, we find that letter writing also leads to more giving if the person is treated unkindly by being assigned to a frustrating rather than a pleasant job. Being able to write, however, does not affect self-reported happiness differently from having to wait. Even more strikingly, subjects assigned to pleasant jobs also give more when writing rather than waiting. This is not consistent with emotional regulation.
Keywords: D91; C91; D03; 330; experimental economics; chain of unkindness; emotional closure; cooling down